Molybdenum-based inferior oil slurry reactor hydrocracking catalyst, preparation method and application method

By mixing the hydrocracked tailings of the slurry bed with naphtha, dissolved with ammonia after calcination, adding zinc nitrate and dimethylimidazole in methanol solution, the ZIF-8 coated molybdenum salt catalyst was prepared, and the existing technology was solved. The high production cost and complex process of molybdenum-based catalysts have achieved efficient recovery and high dispersion of molybdenum-based catalysts, and are suitable for low-cost slurry bed hydrocracking processes with high metals, high residual carbon, and high sulfur inferior oils.

CN119140085AActive Publication Date: 2024-12-17PETROCHINA CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202310719191.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-16
Publication Date
2024-12-17
Estimated Expiration
2043-06-16

AI Technical Summary

Technical Problem

The existing molybdenum-based inferior oil slurry bed hydrocracking catalyst has high production costs and the catalyst preparation process is complex, which affects the economics of the process and environmental benefits.

Method used

The precursor of ZIF-8 coated molybdenum salt was prepared by mixing the slurry bed with naphtha, dissolved with ammonia after calcination, and reacting with zinc nitrate and dimethylimidazole in methanol solution, and in the absence of The hydrocracking catalyst of molybdenum-based inferior oil slurry bed was prepared.

Benefits of technology

It realizes efficient recycling and high dispersion of molybdenum-based catalysts, reduces production costs, and is suitable for low-cost slurry bed hydrocracking process of high metals, high residual carbon, and high sulfur inferior oil. It has simple process, mild conditions and metallic Advantages of high molybdenum recovery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119140085A_ABST
    Figure CN119140085A_ABST
Patent Text Reader

Abstract

The invention discloses a molybdenum-based inferior oil slurry reactor hydrocracking catalyst, a preparation method and an application method, and the preparation method comprises the following steps: mixing slurry reactor hydrocracking tailings with naphtha obtained by the process, and separating to remove oil in the tailings to obtain solid residues; roasting in an air atmosphere to obtain solid powder; under the stirring condition, dissolving each gram of the solid powder by using 2-6ml of ammonia water, and controlling the dissolving temperature to be 50-100 DEG C and dissolving for 1-6 hours to obtain a first mixture; filtering to obtain a dissolving solution; under a stirring condition, adding a methanol solution of zinc nitrate and dimethylimidazole into the dissolved solution; reacting at room temperature for 4-12 hours to obtain a second mixture; filtering to obtain a precipitate in the second mixture; the precipitate is dried for 1-12 h at the temperature of 60-150 DEG C, and a catalyst precursor of ZIF-8 coated molybdenum salt is prepared; and roasting the catalyst precursor of the ZIF-8 coated molybdenum salt in an oxygen-free atmosphere at 400-800 DEG C for 1-6 hours to obtain the molybdenum-based poor-quality oil slurry reactor hydrocracking catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of low-quality oil processing, and in particular to a molybdenum-based low-quality oil slurry bed hydrocracking catalyst, a preparation method and an application method. Background Art

[0002] In view of the increasing number of low-quality crude oil resources with high sulfur, high metal content and high residual carbon, the low-quality oil slurry bed hydrocracking technology is an appropriate process technology that meets the current trend of efficient resource utilization. The key to the development of low-quality oil slurry bed hydrocracking process lies in the continuous improvement of hydrogenation catalysts. Among them, highly dispersed catalysts can be effectively dispersed in heavy raw materials, showing excellent hydrocracking activity and condensation coking inhibition performance, and are more ideal catalysts. However, the production cost of this type of catalyst is significantly affected by the market price fluctuations of metals such as molybdenum, tungsten and nickel, and its preparation price is relatively high. At the same time, in order to maintain a high hydrogenation activity, the reaction system needs to continuously inject a certain concentration of catalyst into the reaction system, resulting in an increase in the processing cost of the process without obvious economic advantages.

[0003] For example, Chinese patent CN201610804914.2 discloses using a soluble salt of Mo or W to precipitate at 40-100°C to prepare an active metal precursor by reacting with C6~C 20 Oil-soluble catalysts are prepared by organic acid reaction. Chinese patent CN201410216485.8 discloses the use of reduced metals and organic amines to react to prepare oil-soluble catalysts. Chinese patent CN201510848631.3 discloses the use of metal salts and carboxylic acid organics, alcohols and sulfiding agents to react to prepare oil-soluble catalysts. Chinese patent CN01106013.1 discloses the use of Mo and W metals and phenylhydroxylamine and its derivatives to react to prepare oil-soluble catalysts. Summary of the invention

[0004] In order to enrich the process routes and increase the selection space, the embodiments of the present invention provide a molybdenum-based low-quality oil slurry bed hydrocracking catalyst, a preparation method and an application method.

[0005] In a first aspect, an embodiment of the present invention provides a method for preparing a molybdenum-based inferior oil slurry bed hydrocracking catalyst, which may include:

[0006] The slurry bed hydrocracking tailings are mixed with the naphtha produced by the slurry bed hydrocracking, and then the oil content in the tailings is removed by separation to obtain a solid residue;

[0007] calcining the solid residue in an air atmosphere to obtain a solid powder;

[0008] Dissolving the calcined solid powder with 2 to 6 ml of aqueous ammonia per gram of solid powder under stirring conditions, and controlling the dissolving temperature to be 50 to 100° C. for 1 to 6 hours to obtain a first mixture;

[0009] filtering the first mixture to obtain a dissolved solution;

[0010] Under stirring conditions, adding a methanol solution of zinc nitrate and dimethylimidazole to the dissolved solution; and reacting at room temperature for 4 to 12 hours to obtain a second mixture;

[0011] filtering the second mixture to obtain a precipitate in the second mixture;

[0012] Drying the precipitate at 60 to 150° C. for 1 to 12 hours to prepare a catalyst precursor of ZIF-8 coated with molybdenum salt;

[0013] The ZIF-8 coated molybdenum salt catalyst precursor is calcined at a calcination temperature of 400 to 800° C. for 1 to 6 hours in an oxygen-free atmosphere to obtain a molybdenum-based inferior oil slurry bed hydrocracking catalyst.

[0014] Optionally, the molar ratio of the zinc nitrate to the molybdenum in the dissolving solution is 4 to 16:1, and the molar ratio of the dimethylimidazole to the zinc nitrate is 3 to 6:1.

[0015] Optionally, the method may further include: dissolving the calcined solid powder under stirring conditions using 4 to 6 ml of aqueous ammonia per gram of solid powder, and controlling the dissolving temperature to be 70 to 90° C. and dissolving for 2 to 4 hours to obtain a first mixture;

[0016] filtering the first mixture to obtain a dissolved solution;

[0017] Under stirring conditions, adding a methanol solution of zinc nitrate and dimethylimidazole to the dissolved solution; and reacting at room temperature for 4 to 6 hours to obtain a second mixture;

[0018] filtering the second mixture to obtain a precipitate in the second mixture;

[0019] Drying the precipitate at 95-120° C. for 4-6 hours to prepare a catalyst precursor of ZIF-8 coated with molybdenum salt;

[0020] The ZIF-8 coated molybdenum salt catalyst precursor is calcined at a calcination temperature of 450 to 650° C. for 3 to 6 hours in an oxygen-free atmosphere to obtain a molybdenum-based inferior oil slurry bed hydrocracking catalyst.

[0021] Optionally, the molar ratio of the zinc nitrate to the molybdenum in the dissolving solution is 5 to 10:1, and the molar ratio of the dimethylimidazole to the zinc nitrate is 4 to 6:1.

[0022] Optionally, the mass ratio of the naphtha to the slurry bed hydrocracking tailings is 1 to 6:1.

[0023] Optionally, the mass ratio of the naphtha to the slurry bed hydrocracking tailings is 1 to 2:1.

[0024] Optionally, when separating and removing the oil from the tailings, the temperature for performing the separation operation on the oil is 70-100°C.

[0025] Optionally, when separating and removing the oil in the tailings, the temperature for performing the separation operation on the oil is 70-90°C.

[0026] Optionally, the solid residue is calcined in an air atmosphere at a calcination temperature of 400 to 800° C. for 1 to 6 hours to obtain a solid powder.

[0027] Optionally, the solid residue is calcined in an air atmosphere at a calcination temperature of 450 to 650° C. for 2 to 4 hours to obtain a solid powder.

[0028] In a second aspect, an embodiment of the present invention provides a molybdenum-based low-quality oil slurry bed hydrocracking catalyst, wherein the molybdenum-based low-quality oil slurry bed hydrocracking catalyst is prepared according to the preparation method of the molybdenum-based low-quality oil slurry bed hydrocracking catalyst described in the first aspect.

[0029] In a third aspect, an embodiment of the present invention provides a method for applying a molybdenum-based low-quality oil slurry bed hydrocracking catalyst in a low-quality oil processing technology, wherein the molybdenum-based low-quality oil slurry bed hydrocracking catalyst is uniformly mixed with a diesel fraction produced by slurry bed hydrocracking at a volume ratio of 0.05 to 0.2:1 and then added to the low-quality oil raw material;

[0030] Wherein, the molybdenum-based low-quality oil slurry bed hydrocracking catalyst is prepared according to the preparation method of the molybdenum-based low-quality oil slurry bed hydrocracking catalyst described in the first aspect.

[0031] Optionally, the molybdenum-based low-quality oil slurry bed hydrocracking catalyst is used in an amount of 200 to 1000 μg / g in terms of metal molybdenum, and the process conditions are: reaction pressure 10 to 20 MPa, reaction temperature 360 ​​to 450°C, volume space velocity 0.2 to 1.0 h -1 , hydrogen-oil volume ratio is 300~1000.

[0032] Optionally, the molybdenum-based low-quality oil slurry bed hydrocracking catalyst is uniformly mixed with a diesel fraction at a volume ratio of 0.05 to 0.1:1 and then added to the low-quality oil feedstock.

[0033] Optionally, the molybdenum-based low-quality oil slurry bed hydrocracking catalyst is used in an amount of 300-600 μg / g in terms of metal molybdenum, and the process conditions are: reaction pressure 10-16 MPa, reaction temperature 390-420°C, volume space velocity 0.2-0.5 h -1 , hydrogen-oil volume ratio is 300~500.

[0034] The beneficial effects of the above technical solution provided by the embodiment of the present invention include at least:

[0035] The embodiment of the present invention provides a molybdenum-based low-quality oil slurry bed hydrocracking catalyst, a preparation method and an application method, the preparation method has the advantages of simple process, mild conditions, high metal molybdenum recovery rate, and convenience for low-cost industrial application. The prepared molybdenum-based catalyst has excellent hydrogenation performance and is particularly suitable for low-cost slurry bed hydrocracking process of high-metal, high-carbon residue, and high-sulfur low-quality oil.

[0036] Specifically, the preparation method of the molybdenum-based inferior oil slurry bed hydrocracking catalyst and the prepared catalyst in the embodiment of the present invention have the following beneficial effects:

[0037] (1) The slurry bed hydrocracking tailings are mixed with the naphtha produced by the unit, which is conducive to the efficient separation of the oil in the tailings and the metal-rich solid residue.

[0038] (2) The waste catalyst contained in the solid residue can be efficiently recovered as metallic molybdenum through calcination and ammonia dissolution.

[0039] (3) The use of metal framework materials to coat active metal molybdenum salts can effectively inhibit the aggregation and growth of molybdenum, construct a carbon-supported catalyst in which the active component molybdenum is dispersed in a single atom, has excellent hydrogenation activity and coke inhibition performance, and realizes the efficient reuse of molybdenum-based catalysts.

[0040] (4) Using self-produced diesel fractions to disperse and carry the slurry bed catalyst prepared by the present invention, and then injecting it into the inferior residual oil raw material, since the diesel fraction used as a carrier or dispersant is derived from the inferior residual oil, it is more conducive to the dispersion of the catalyst in the raw material in terms of the original factors of the hydrocarbon group composition, which is beneficial to the high dispersion and efficient utilization of the catalyst.

[0041] (5) The present invention provides a method for preparing a molybdenum-based slurry bed hydrocracking catalyst from slurry bed hydrocracking tailings and an application method thereof, which has the advantages of simple process, mild conditions, high recovery rate of metal molybdenum, online recovery of active metals and preparation of catalysts or offline recovery of active metals and preparation of catalysts, and convenience for low-cost industrial applications.

[0042] (6) The molybdenum-based catalyst prepared by the present invention has the characteristics of small addition amount and simple application, and is suitable for the slurry bed hydrocracking process of high-metal, high-carbon residue, high-sulfur low-quality oil.

[0043] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structures particularly pointed out in the written description and the accompanying drawings.

[0044] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:

[0046] Figure 1 The present invention provides a schematic diagram of the process flow of preparing a molybdenum-based low-quality oil slurry bed hydrocracking catalyst and its application. DETAILED DESCRIPTION

[0047] The exemplary embodiments of the present disclosure will be described in more detail below with reference to the accompanying drawings. Although the exemplary embodiments of the present disclosure are shown in the accompanying drawings, it should be understood that the present disclosure can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to enable a more thorough understanding of the present disclosure and to fully convey the scope of the present disclosure to those skilled in the art.

[0048] The inventors summarized the reported oil-soluble catalysts and believed that they are mainly organic acid salts, organometallic compounds or complexes, and metal salts of organic amines as precursors. Although such oil-soluble catalysts show excellent hydrocracking performance, the precursors need to add a sulfiding agent to be converted into catalytically active metal sulfides. Due to the difficulty of sulfurization, the final sulfide particle size is relatively large in this process, which reduces the catalytic hydrogenation activity, resulting in a large amount of addition and increasing the cost of the operation. Therefore, the preparation of a highly dispersed inferior oil slurry bed hydrocracking catalyst with high activity is a technical problem that needs to be solved in the art.

[0049] At present, the inferior oil slurry bed hydrogenation process generally produces 1 to 10 wt% hydrocracking tailings when treating inferior heavy raw materials. This fraction is enriched with impurities such as coke, deactivated catalysts and metals generated during the reaction. How to achieve high-value utilization of solid impurities and valuable metals in hydrocracking tailings will be the key to affecting the economic efficiency of slurry bed hydrogenation technology. At the same time, with the increasingly stringent environmental protection regulations, the harmless treatment of industrial waste has attracted people's attention. If the solids in the slurry bed hydrocracking tailings are not treated, they will inevitably pollute the environment. Moreover, the solids contain high-value active metals, and efficient recycling will inevitably produce huge economic and social benefits. Therefore, the resource utilization of hydrocracking tailings has always been a matter of great concern to researchers.

[0050] In response to the above technical problems, some technical solutions have been proposed in the prior art. For example, the technical solution disclosed in the application number 20171080154.1 and the invention name "Method for recycling oil-soluble molybdenum-based slurry bed hydrocracking catalyst" is as follows: the waste catalyst is subjected to roasting, ammonia dissolution, and sulfurization processes to obtain a sulfide metal salt of molybdenum, and then the sulfide metal salt of molybdenum is reacted with an organic acid to prepare a precursor of an oil-soluble molybdenum-based catalyst. The precursor is self-sulfurized and decomposed in inferior oil to form a nano-dispersed catalyst, and finally the waste catalyst is reused. The inventor found that the defects of the technical solution are as follows: the method of preparing the catalyst raw material slurry bed waste catalyst of the method first does not clearly explain the method of obtaining it, and there is a technical bottleneck in the efficient separation of the waste catalyst from the slurry bed hydrocracking tailings; in addition, the method requires the addition of a sulfiding agent and an organic acid to prepare a highly dispersed oil-soluble slurry bed hydrocracking catalyst. Due to the need to consume a large amount of high-value sulfiding agents and organic acids, the preparation cost is relatively high compared to fresh catalysts.

[0051] For example, the technical solution disclosed in the application number 20171124760.0 and the invention name "Recovery and application of metals in suspended bed or slurry bed hydrocracking residue" is as follows: the suspended bed or slurry bed hydrocracking residue is digested by different digestion liquids to recover the molybdenum or molybdenum and nickel metals contained in the residue, and then a reducing agent is added to carry out a reduction reaction, and then the slurry bed catalyst is obtained after washing and injected into the raw material system to realize the recycling utilization of the catalyst. The inventors found that the technical solution firstly needs to use two types of high-value digestion solutions, one of which is a mixture containing water, alcohol and amine, wherein the alcohol and amine include a variety of organic reagents, and the other is an alkaline or acidic digestion solution, which contains reagents such as urea, ammonia, sulfuric acid, ethanol and water; secondly, the method needs to consume a large amount of reducing agents, including inorganic sulfides such as sodium hydrosulfide, sodium thiosulfate, carbon disulfide, sodium sulfite, sodium bisulfite, sodium sulfide, sodium disulfide, and thiourea dioxide; in summary, the slurry bed hydrocracking catalyst prepared by the method has a complex process and a long process flow, and the use of various reagents is large, resulting in its environmental benefits, economic benefits and technological advancement have no obvious advantages. Based on this, the inventors proposed the present invention.

[0052] Reference Figure 1 As shown, the process steps of the preparation method of the molybdenum-based low-quality oil slurry bed hydrocracking catalyst and the application method of the molybdenum-based low-quality oil slurry bed hydrocracking catalyst in the low-quality oil processing technology in the embodiment of the present invention are as follows:

[0053] (1) The tailings from the fractionation system of the inferior oil slurry bed hydrocracking process are subjected to the process of removing the oil from the self-produced naphtha of the device to obtain a solid residue;

[0054] (2) the solid residue is subjected to oxygen roasting to obtain a solid powder;

[0055] (3) using aqueous ammonia to dissolve the metallic molybdenum in the solid powder to obtain a dissolved solution;

[0056] (4) adding a methanol solution of zinc nitrate and dimethylimidazole to the dissolved solution to react and prepare a catalyst precursor C1;

[0057] (5) C1 is calcined under oxygen-free conditions to prepare a slurry bed hydrocracking catalyst C2.

[0058] The source information of raw materials or equipment in the examples of the present invention is shown in Table 1.

[0059] Table 1 Raw materials and equipment information

[0060]

[0061] The evaluation and analysis method for the prepared catalyst in the embodiment of the present invention is as follows:

[0062] The test raw materials and the prepared slurry bed catalyst were analyzed and tested according to the national standards and conventional test methods in this technical field, and the catalyst cracking performance was evaluated using a slurry bed pilot plant (in the embodiment of the present invention, the tailings produced by a 100-ton slurry bed pilot plant were used as the raw material for preparing the molybdenum-based inferior oil slurry bed hydrocracking catalyst). Specific embodiment:

[0064] After naphtha and slurry bed hydrocracking tailings are mixed in different mass ratios, the oil is separated and removed at 80°C to obtain a solid residue. In the embodiment of the present invention, a hydrocyclone separator, a centrifuge, a plate and frame filter press, etc. can be used to separate and remove the solid residue. The oil temperature during the separation operation is 70-100°C. The deoiling test results are shown in Table 2.

[0065] Table 2 Slurry bed hydrocracking tailings deoiling test results

[0066]

[0067] Note: Separation time refers to the total working time of removing oil from hydrocracking tailings using naphtha.

[0068] The solid residue was calcined in air atmosphere in two stages: (1) calcined at 400°C for 0.5 hours and 600°C for 0.5 hours to obtain solid powder G1-1; (2) calcined at 400°C for 1 hour and 600°C for 1 hour to obtain solid powder G1-2; (3) calcined at 450°C for 2 hours and 650°C for 2 hours to obtain solid powder G1-3; (4) calcined at 550°C for 2 hours and 700°C for 2 hours to obtain solid powder G1-4; (5) calcined at 550°C for 3 hours and 800°C for 3 hours to obtain solid powder G1-5. The composition of solid powder G1 is shown in Table 3.

[0069] Table 3 Analysis of the solid content in the slurry bed hydrocracking tailings calcined in air atmosphere

[0070]

[0071] Example 1

[0072] Weigh 100g of solid powder G1 from the slurry bed hydrocracking tailings, dissolve the calcined solid powder in ammonia water under stirring, ammonia water / solid powder = 2 / 1 (mL / g), dissolution temperature 50°C, dissolution time 1 hour, obtain dissolution liquid Y1 and ammonia insolubles, filter and separate. Add zinc nitrate and dimethylimidazole methanol solution to the dissolution liquid Y1, the molar ratio of zinc nitrate to molybdenum = 4 / 1, the molar ratio of dimethylimidazole to zinc nitrate = 3 / 1. Stir the reaction for 4 hours at room temperature. Filter the resulting turbid liquid with a Buchner funnel, wash with distilled water, dry at 60°C, and dry for 1 hour. Then roast in an oxygen-free atmosphere, roast at 400°C, roast for 1 hour, and obtain the carbon-supported catalyst C2-1 in which the active component molybdenum is dispersed in a single atom. The recovery rate of metallic molybdenum is 80.1%.

[0073] Example 2

[0074] Weigh 100g of solid powder G1 from the slurry bed hydrocracking tailings, dissolve the calcined solid powder in ammonia water under stirring, ammonia water / solid powder = 2 / 1 (mL / g), dissolution temperature 50°C, dissolution time 1 hour, obtain dissolution liquid Y1 and ammonia insolubles, filter and separate. Add zinc nitrate and dimethylimidazole methanol solution to the dissolution liquid Y1, the molar ratio of zinc nitrate to molybdenum = 4 / 1, the molar ratio of dimethylimidazole to zinc nitrate = 3 / 1. Stir the reaction for 4 hours at room temperature. Filter the resulting turbid liquid with a Buchner funnel, wash with distilled water, dry at 60°C, and dry for 1 hour. Then roast in an oxygen-free atmosphere, roast at 450°C, roast for 1.5 hours, and obtain the carbon-supported catalyst C2-2 in which the active component molybdenum is dispersed in a single atom. The recovery rate of metallic molybdenum is 80.6%.

[0075] Example 3

[0076] Weigh 100g of solid powder G1 from the slurry bed hydrocracking tailings, dissolve the calcined solid powder in ammonia water under stirring, ammonia water / solid powder = 3 / 1 (mL / g), dissolution temperature 70°C, dissolution time 2 hours, obtain dissolution liquid Y1 and ammonia insolubles, filter and separate. Add zinc nitrate and dimethylimidazole methanol solution to the dissolution liquid Y1, the molar ratio of zinc nitrate to molybdenum = 5 / 1, the molar ratio of dimethylimidazole to zinc nitrate = 4 / 1. Stir the reaction for 4.5 hours at room temperature. Filter the resulting turbid liquid with a Buchner funnel, wash with distilled water, dry at 95°C, and dry for 4 hours. Then roast in an oxygen-free atmosphere, roast at 600°C, roast for 2 hours, and obtain a carbon-supported catalyst C2-3 in which the active component molybdenum is dispersed in a single atom. The recovery rate of metallic molybdenum is 85.5%.

[0077] Example 4

[0078] Weigh 100g of solid powder G1 from the slurry bed hydrocracking tailings, dissolve the solid powder obtained by calcination in ammonia water under stirring, ammonia water / solid powder = 3 / 1 (mL / g), dissolution temperature 70°C, dissolution time 2 hours, obtain dissolution liquid Y1 and ammonia insolubles, filter and separate. Add zinc nitrate and dimethylimidazole methanol solution to the dissolution liquid Y1, the molar ratio of zinc nitrate to molybdenum = 5 / 1, the molar ratio of dimethylimidazole to zinc nitrate = 4 / 1. Stir the reaction for 4.5 hours at room temperature. Filter the obtained turbid liquid with a Buchner funnel, wash with distilled water, dry at 95°C, and dry for 4 hours. Then roast in an oxygen-free atmosphere, roast at 650°C, roast for 2.5 hours, and obtain the carbon-supported catalyst C2-4 in which the active component molybdenum is dispersed in a single atom. The recovery rate of metallic molybdenum is 86.4%.

[0079] Example 5

[0080] Weigh 100g of solid powder G1 from the slurry bed hydrocracking tailings, dissolve the solid powder obtained by calcination in ammonia water under stirring, ammonia water / solid powder = 4 / 1 (mL / g), dissolution temperature 80°C, dissolution time 2 hours, obtain dissolution liquid Y1 and ammonia insolubles, filter and separate. Add zinc nitrate and dimethylimidazole methanol solution to the dissolution liquid Y1, the molar ratio of zinc nitrate to molybdenum = 8 / 1, the molar ratio of dimethylimidazole to zinc nitrate = 4 / 1. Stir the reaction for 6 hours at room temperature. Filter the obtained turbid liquid with a Buchner funnel and wash with distilled water, drying temperature 100°C, drying time 4.5 hours. Then roast in an oxygen-free atmosphere, roasting temperature 750°C, roasting time 3 hours, and obtain the carbon-supported catalyst C2-5 in which the active component molybdenum is dispersed in a single atom. The recovery rate of metallic molybdenum is 95.5%.

[0081] Example 6

[0082] Weigh 100g of solid powder G1 from the slurry bed hydrocracking tailings, dissolve the calcined solid powder in ammonia water under stirring, ammonia water / solid powder = 4 / 1 (mL / g), dissolution temperature 80°C, dissolution time 3 hours, obtain dissolution liquid Y1 and ammonia insolubles, filter and separate. Add zinc nitrate and dimethylimidazole methanol solution to the dissolution liquid Y1, the molar ratio of zinc nitrate to molybdenum = 10 / 1, the molar ratio of dimethylimidazole to zinc nitrate = 5 / 1. Stir the reaction for 8 hours at room temperature. Filter the resulting turbid liquid with a Buchner funnel, wash with distilled water, dry at 120°C, and dry for 6 hours. Then roast in an oxygen-free atmosphere, roast at 800°C, roast for 4 hours, and obtain the carbon-supported catalyst C2-6 in which the active component molybdenum is dispersed in a single atom. The recovery rate of metallic molybdenum is 97.4%.

[0083] Example 7

[0084] Weigh 100g of solid powder G1 from the slurry bed hydrocracking tailings, dissolve the roasted solid powder in ammonia water under stirring, ammonia water / solid powder = 5 / 1 (mL / g), dissolution temperature 90°C, dissolution time 4 hours, obtain dissolution liquid Y1 and ammonia insolubles, filter and separate. Add zinc nitrate and dimethylimidazole methanol solution to the dissolution liquid Y1, the molar ratio of zinc nitrate to molybdenum = 12 / 1, the molar ratio of dimethylimidazole to zinc nitrate = 5 / 1. Stir the reaction for 12 hours at room temperature. Filter the resulting turbid liquid with a Buchner funnel, wash with distilled water, dry at 120°C, and dry for 12 hours. Then roast in an oxygen-free atmosphere, roast at 800°C, roast for 3 hours, and obtain the carbon-supported catalyst C2-7 in which the active component molybdenum is dispersed in a single atom. The recovery rate of metallic molybdenum is 98.9%.

[0085] Example 8

[0086] Weigh 100g of solid powder G1 from the slurry bed hydrocracking tailings, dissolve the solid powder obtained by roasting in ammonia water under stirring, ammonia water / solid powder = 6 / 1 (mL / g), dissolution temperature 100°C, dissolution time 6 hours, obtain dissolution liquid Y1 and ammonia insolubles, filter and separate. Add zinc nitrate and dimethylimidazole methanol solution to the dissolution liquid Y1, the molar ratio of zinc nitrate to molybdenum = 16 / 1, the molar ratio of dimethylimidazole to zinc nitrate = 6 / 1. Stir the reaction for 12 hours at room temperature. Filter the obtained turbid liquid with a Buchner funnel, wash with distilled water, dry at 150°C, and dry for 12 hours. Then roast in an oxygen-free atmosphere, roast at 800°C, roast for 6 hours, and obtain the carbon-supported catalyst C2-8 in which the active component molybdenum is dispersed in a single atom. The recovery rate of metallic molybdenum is 99.1%.

[0087] Comparative Example 1

[0088] Weigh 50g of molybdenum trioxide, dissolve the molybdenum trioxide in ammonia water under stirring, ammonia water / molybdenum trioxide = 4 / 1 (mL / g), dissolution temperature 80°C, dissolution time 2 hours, and obtain solution Y1. Add methanol solution of zinc nitrate and dimethylimidazole to solution S1, the molar ratio of zinc nitrate to molybdenum = 8 / 1, and the molar ratio of dimethylimidazole to zinc nitrate = 4 / 1. Stir the reaction for 12 hours at room temperature. Filter the resulting turbid liquid with a Buchner funnel and wash with distilled water, drying temperature 100°C, drying time 6 hours. Then roast in an oxygen-free atmosphere, roasting temperature 800°C, roasting time 3 hours, to obtain a carbon-supported catalyst CD-1 in which the active component molybdenum is dispersed in a single atom.

[0089] Comparative Example 2

[0090] Weigh 100g of solid powder G1 from the slurry bed hydrocracking tailings, dissolve the solid powder obtained by roasting in ammonia water under stirring conditions, ammonia water / solid powder = 1 / 1 (mL / g), dissolution temperature 40°C, dissolution time 0.5 hour, obtain dissolution liquid Y1 and ammonia insolubles, filter and separate. Add zinc nitrate and dimethylimidazole methanol solution to the dissolution liquid Y1, the molar ratio of zinc nitrate to molybdenum = 2 / 1, the molar ratio of dimethylimidazole to zinc nitrate = 2 / 1. Stir the reaction for 2 hours at room temperature. Filter the resulting turbid liquid with a Buchner funnel and wash with distilled water, drying temperature 40°C, drying time 0.5 hour. Then roast in an oxygen-free atmosphere, roasting temperature 350°C, roasting time 1 hour, and obtain the carbon-supported catalyst CD-2 in which the active component molybdenum is dispersed in a single atom. The recovery rate of metallic molybdenum is 69.2%.

[0091] Comparative Example 3

[0092] Weigh 100g of solid powder G1 from the slurry bed hydrocracking tailings, dissolve the solid powder obtained by calcination in ammonia water under stirring, ammonia water / solid powder = 10 / 1 (mL / g), dissolution temperature 120°C, dissolution time 10 hours, obtain dissolution liquid Y1 and ammonia insolubles, filter and separate. Add zinc nitrate and dimethylimidazole methanol solution to the dissolution liquid Y1, the molar ratio of zinc nitrate to molybdenum = 20 / 1, the molar ratio of dimethylimidazole to zinc nitrate = 10 / 1. Stir the reaction for 20 hours at room temperature. Filter the obtained turbid liquid with a Buchner funnel, wash with distilled water, dry at 180°C, and dry for 20 hours. Then roast in an oxygen-free atmosphere, roast at 850°C, roast for 8 hours, and obtain a carbon-supported catalyst CD-3 in which the active component molybdenum is dispersed in a single atom. The recovery rate of metallic molybdenum is 99.2%.

[0093] The molybdenum-based catalysts (C2-1, C2-2, C2-3, C2-4, C2-5, C2-6, C2-7, C2-8, CD-1, CD-2, CD-3) in Examples 1 to 8 and Comparative Examples 1 to 3 were used, mixed vacuum residue was used as raw material (properties are shown in Table 4), and a slurry bed small test device was used. The reaction temperature was 420°C, the reaction pressure was 16 MPa, the catalyst dosage was 500 μg / g in terms of metal molybdenum, and the space velocity was 0.5 h -1 The hydrocracking test was carried out under the conditions of 500:hydrogen-to-oil volume ratio. The evaluation results of vacuum residue hydrocracking over different catalysts are shown in Table 5.

[0094] Table 4 Properties of mixed vacuum residue

[0095]

[0096]

[0097] Note: The mixed vacuum residue oil is prepared by mixing Venezuelan vacuum residue oil, Karamay vacuum residue oil and West Pacific vacuum residue oil in a mass ratio of 3:1:1.

[0098] Table 5 Vacuum residue hydrocracking evaluation results

[0099]

[0100]

[0101] As shown in Examples 1 to 8, the catalyst prepared by the preparation method provided by the present invention can realize the efficient recovery of the deactivated molybdenum-based catalyst in the slurry bed hydrocracking tailings, and the recovery rate of molybdenum is higher than 80%. With the optimization of process parameters, the recovery rate of molybdenum is higher than 95.5%. As shown in Table 5, the molybdenum-based catalyst prepared by the slurry bed hydrocracking tailings provided by the present invention has good hydrogenation performance and coke inhibition ability, which is equivalent to the activity and coke inhibition ability of the molybdenum-based catalyst prepared by pure molybdenum trioxide (Comparative Example 1). The catalyst prepared by the process tailings in the embodiment of the present invention can save a lot of resource costs and has significant progress. Under the same reaction conditions, the single-pass conversion rate of vacuum residue is>63wt%, and the coke rate is<0.5wt%. The above data show that the recycling method of the molybdenum-based catalyst involved in the embodiment of the present invention has the advantages of simple process, mild conditions, high recovery rate of metal molybdenum, and convenience for low-cost industrial application. However, as the process parameters continue to increase, such as the increase in the volume of ammonia water, the enhancement of dissolution conditions, the increase in the amount of zinc nitrate and dimethylimidazole, the enhancement of drying conditions, and the enhancement of anaerobic roasting conditions, the increase in the recovery rate of molybdenum is no longer obvious, but the economic cost increases relatively significantly; at the same time, the inventors found that after the anaerobic roasting conditions are enhanced, the metal molybdenum crystal nucleus is damaged, physical recrystallization occurs, and the requirements of fine particle size and high dispersion properties cannot be achieved.

[0102] In summary, the molybdenum-based catalyst prepared in the embodiment of the present invention has excellent hydrogenation performance, and is particularly suitable for low-cost slurry bed hydrocracking process of high-metal, high-carbon residue, high-sulfur inferior oil. And compared with the oil-soluble catalyst prepared in the "Method for Recycling of Oil-Soluble Molybdenum-Based Slurry Bed Hydrocracking Catalyst", the highly dispersed catalyst prepared by tailings in the embodiment of the present invention can be effectively dispersed in heavy raw materials, not only showing excellent hydrocracking activity and condensation coke inhibition performance, but also saving a lot of resource costs, and is suitable for large-scale promotion and use.

[0103] At the same time, the inventors analyzed the technical solutions disclosed in the patent document with the publication number CN108441884A and the invention name "Molybdenum disulfide / carbon composite hydrogen evolution electrocatalyst and preparation method thereof" in the prior art. The technical solutions disclosed in the patent are as follows: (1) Preparation of carbon: using deionized water as a solvent, preparing a mixed solution of zinc salt and dimethylimidazole, stirring the reaction, and separating the solid substance is the metal organic framework material ZIF-8; the metal organic framework material ZIF-8 is calcined at a high temperature, and then cleaned After washing and drying, a carbon material is obtained; (2) preparing a molybdenum disulfide / carbon composite material by a hydrothermal method: using deionized water as a solvent, preparing a mixed solution of sodium molybdate tetrahydrate and thiourea, wherein the mass ratio of sodium molybdate tetrahydrate to thiourea is 1:1.5 to 1:3; placing the mixed solution together with the carbon material prepared in step (1) in a reactor for a hydrothermal reaction, filtering the obtained product, washing with deionized water, and drying to obtain a molybdenum disulfide / carbon composite material; wherein the mass ratio of sodium molybdate tetrahydrate to carbon material is 15:1 to 2:1.

[0104] The inventor has carefully read the patent with publication number CN108441884A and believes that it belongs to the field of electrocatalytic hydrogen evolution technology. The preparation method is based on the metal organic framework material ZIF-8 prepared from a mixed solution of zinc salt and dimethylimidazole, which is a carbon-coated zinc salt catalyst (carbon material), and then this is used as a carrier to load molybdenum disulfide thereon, thereby finally generating a molybdenum disulfide / carbon composite material.

[0105] After comparison, the inventor believes that the embodiments of the present invention and the CN108441884A patent have at least the following differences: (1) The catalyst precursor of the ZIF-8 coated molybdenum salt in the embodiments of the present invention is prepared based on the metallic molybdenum extracted from the waste. Molybdenum itself is a precious metal, and its preparation cost is different, and the final catalyst components are also completely different; (2) The catalyst precursor of the ZIF-8 coated molybdenum salt prepared in the embodiments of the present invention is then subjected to oxygen-free calcination to obtain a highly dispersed catalyst, while the CN108441884A patent does not have this step; (3) In the process of preparing the catalyst precursor of the ZIF-8 coated molybdenum salt in the embodiments of the present invention, zinc in zinc nitrate is used as an auxiliary agent, and its main purpose is to provide a catalyst to improve the high dispersion of the molybdenum element. The competitive coefficient auxiliary agent is an auxiliary agent added to increase the loading rate of the main active metal in the supported catalyst, so that the molybdenum atoms are more evenly dispersed on the carrier. The molybdenum atoms are the main body of the ZIF-8 framework; while the catalyst of the carbon-coated zinc salt in the CN108441884A patent, the zinc atom is the main active metal, which is the main body of the ZIF-8 framework, and there is an essential difference between the ZIF-8 frameworks of the two; (4) The final product prepared in the embodiment of the present invention is carbon-supported molybdenum (ZIF-8 framework), while the molybdenum disulfide supported by the ZIF-8 framework (carbon-coated zinc salt) in the CN108441884A patent, and the structure, use, and function of the above-mentioned molybdenum-based catalyst and the molybdenum disulfide / carbon composite material are completely different. In summary, the inventive concept of the molybdenum-based catalyst preparation scheme in the CN108441884A patent and the embodiment of the present invention is completely different.

[0106] For those skilled in the art, the specific embodiments are only exemplary descriptions of the present invention. Obviously, the specific implementation of the present invention is not limited by the above-mentioned methods. As long as various non-substantial improvements are made using the method concept and technical solution of the present invention, or the concept and technical solution of the present invention are directly applied to other occasions without improvement, they are all within the protection scope of the present invention. That is, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. In this way, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalent technologies, the present invention is also intended to include these changes and variations.

Claims

1. A method for preparing a molybdenum-based low-quality oil slurry bed hydrocracking catalyst, It is characterized in that include: The slurry bed hydrocracking tailings are mixed with the naphtha produced by the slurry bed hydrocracking, and then the oil content in the tailings is removed by separation to obtain a solid residue; calcining the solid residue in an air atmosphere to obtain a solid powder; Dissolving the calcined solid powder with 2 to 6 ml of aqueous ammonia per gram of solid powder under stirring conditions, and controlling the dissolving temperature to be 50 to 100° C. for 1 to 6 hours to obtain a first mixture; filtering the first mixture to obtain a dissolved solution; Under stirring conditions, adding a methanol solution of zinc nitrate and dimethylimidazole to the dissolved solution; and reacting at room temperature for 4 to 12 hours to obtain a second mixture; filtering the second mixture to obtain a precipitate in the second mixture; Drying the precipitate at 60 to 150° C. for 1 to 12 hours to prepare a catalyst precursor of ZIF-8 coated with molybdenum salt; The ZIF-8 coated molybdenum salt catalyst precursor is calcined at a calcination temperature of 400 to 800° C. for 1 to 6 hours in an oxygen-free atmosphere to obtain a molybdenum-based inferior oil slurry bed hydrocracking catalyst.

2. The method according to claim 1, It is characterized in that The molar ratio of the zinc nitrate to the molybdenum in the dissolving solution is 4-16:1, and the molar ratio of the dimethylimidazole to the zinc nitrate is 3-6:

1.

3. The method according to claim 1, It is characterized in that include: Dissolve the calcined solid powder under stirring conditions, using 4 to 6 ml of aqueous ammonia per gram of solid powder, and control the dissolving temperature to be 70 to 90° C. and dissolving for 2 to 4 hours to obtain a first mixture; filtering the first mixture to obtain a dissolved solution; Under stirring conditions, adding a methanol solution of zinc nitrate and dimethylimidazole to the dissolved solution; and reacting at room temperature for 4 to 6 hours to obtain a second mixture; filtering the second mixture to obtain a precipitate in the second mixture; Drying the precipitate at 95-120° C. for 4-6 hours to prepare a catalyst precursor of ZIF-8 coated with molybdenum salt; The ZIF-8 coated molybdenum salt catalyst precursor is calcined at a calcination temperature of 450 to 650° C. for 3 to 6 hours in an oxygen-free atmosphere to obtain a molybdenum-based inferior oil slurry bed hydrocracking catalyst.

4. The method according to claim 3, It is characterized in that The molar ratio of the zinc nitrate to the molybdenum in the dissolving solution is 5 to 10:1, and the molar ratio of the dimethylimidazole to the zinc nitrate is 4 to 6:

1.

5. The method according to any one of claims 1 to 4, It is characterized in that The mass ratio of the naphtha to the slurry bed hydrocracking tailings is 1 to 6:

1.

6. The method according to claim 5, It is characterized in that The mass ratio of the naphtha to the slurry bed hydrocracking tailings is 1 to 2:

1.

7. The method according to claim 5, It is characterized in that When separating and removing the oil in the tailings, the temperature for performing the separation operation on the oil is 70-100°C.

8. The method according to claim 7, It is characterized in that When separating and removing the oil in the tailings, the temperature for performing the separation operation on the oil is 70 to 90°C.

9. The method according to claim 5, It is characterized in that The solid residue is calcined in an air atmosphere at a calcination temperature of 400 to 800° C. for 1 to 6 hours to obtain a solid powder.

10. The method according to claim 9, It is characterized in that The solid residue is calcined in an air atmosphere at a calcination temperature of 450 to 650° C. for 2 to 4 hours to obtain a solid powder.

11. A molybdenum-based inferior oil slurry bed hydrocracking catalyst, It is characterized in that The molybdenum-based low-quality oil slurry bed hydrocracking catalyst is prepared according to the preparation method of the molybdenum-based low-quality oil slurry bed hydrocracking catalyst according to any one of claims 1 to 10.

12. A method for applying a molybdenum-based low-quality oil slurry bed hydrocracking catalyst in a low-quality oil processing technology, It is characterized in that The molybdenum-based low-quality oil slurry bed hydrocracking catalyst and the diesel fraction produced by slurry bed hydrocracking are uniformly mixed at a volume ratio of 0.05 to 0.2:1, and then added to the low-quality oil raw material; Wherein, the molybdenum-based low-quality oil slurry bed hydrocracking catalyst is prepared according to the preparation method of the molybdenum-based low-quality oil slurry bed hydrocracking catalyst according to any one of claims 1 to 10.

13. The use method according to claim 12, It is characterized in that The molybdenum-based inferior oil slurry bed hydrocracking catalyst is used in an amount of 200-1000 μg / g in terms of metal molybdenum, and the process conditions are: reaction pressure 10-20 MPa, reaction temperature 360-450° C., volume space velocity 0.2-1.0 h -1 , hydrogen-oil volume ratio is 300~1000.

14. The use method according to claim 12, It is characterized in that The molybdenum-based low-quality oil slurry bed hydrocracking catalyst is uniformly mixed with a diesel fraction at a volume ratio of 0.05 to 0.1:1 and then added to the low-quality oil raw material.

15. The use method according to claim 14, It is characterized in that The molybdenum-based inferior oil slurry bed hydrocracking catalyst is used in an amount of 300-600 μg / g in terms of metal molybdenum, and the process conditions are: reaction pressure 10-16 MPa, reaction temperature 390-420° C., volume space velocity 0.2-0.5 h -1 , hydrogen-oil volume ratio is 300~500.

Citation Information

Patent Citations

  • ZIF-8 material-based hydrogenation catalyst and synthetic method thereof

    CN104772165A

  • Surface-amphiphilic nano tungsten molybdenum sulfide hydrogenation catalyst, preparation method and application thereof

    CN105498805A

  • Preparation method of heavy oil suspended bed hydro-cracking catalyst and slurry produced by method

    CN106140184A

  • Recycling method of oil-soluble molybdenum-based slurry reactor hydrocracking catalyst

    CN107486248A

  • Utilization method of hydrocracking molybdenum-containing tailings

    CN114426889A